Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd001055.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for promoting smoking cessation during pregnancy

Abstract: Background Tobacco smoking in pregnancy remains one of the few preventable factors associated with complications in pregnancy, low birthweight, preterm birth and has serious long-term health implications for women and babies. Smoking in pregnancy is decreasing in high-income countries and increasing in low- to middle-income countries and is strongly associated with poverty, low educational attainment, poor social support and psychological illness. Objectives To assess the effects of smoking cessation interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
662
4
18

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 704 publications
(706 citation statements)
references
References 304 publications
(335 reference statements)
22
662
4
18
Order By: Relevance
“…Women commonly modify their substance use during later pregnancy with modest benefits for fetal growth and development 103 . Heavy and dependent users, more common in countries with delayed parenthood, are less likely to cease use during pregnancy 104 .…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
“…Women commonly modify their substance use during later pregnancy with modest benefits for fetal growth and development 103 . Heavy and dependent users, more common in countries with delayed parenthood, are less likely to cease use during pregnancy 104 .…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
“…In a review of 32 papers, Bell et al (2006) suggest quit rates of 23-51% at 52 weeks amongst pregnant women who set a quit date with the UK NHS stop smoking service. In a recent systematic review, Lumley et al (2009) examined the outcomes of randomised controlled trials for smoking cessation interventions during pregnancy. The review reported evidence of a 6% absolute difference in smoking rates in those receiving an intervention relative to a usual care comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Most intervention studies have concentrated on helping pregnant women to quit smoking [2] and on helping husbands to quit [3]. Little has been done, however, to help pregnant women increase the chance that they live in smoke-free homes.…”
Section: Introductionmentioning
confidence: 99%